Facile Access to Dative, Single, and Double Silicon−Metal Bonds Through M−Cl Insertion Reactions of Base‐Stabilized SiII Cations. Issue 28 (28th April 2020) - Frisch, Philipp; Szilvási, Tibor; Inoue, Shigeyoshi
Abstract: Silicon(II) cations can offer fascinating reactivity patterns due to their unique electronic structure: a lone pair of electrons, two empty p orbitals and a positive charge combined on a single silicon center. We now report the facile insertion of N‐heterocyclic carbene (NHC)‐stabilized silyliumylidene ions into M−Cl bonds (M=Ru, Rh), forming a series of novel chlorosilylene transition‐metal complexes. Theoretical investigations revealed a reaction mechanism in which the insertion into the M−Cl bond with concomitant 1, 2‐migration of a silicon‐bound NHC to the transition metal takes place after formation of an initial silyliumylidene transition‐metal complex. The mechanism could be verified experimentally through characterization of the intermediate complexes. Furthermore, the obtained chlorosilylene complexes can be conveniently utilized as synthons to access Si−M and Si=M bonding motifs bonds through reductive dehalogenation. Abstract : A facile access route to Si→M, Si−M, and Si=M (M=Ru, Rh) moieties through the insertion of NHC‐stabilized silyliumylidene ions into metal−chloride bonds and subsequent reductive dehalogenation is reported. The coordination–insertion–migration mechanism was investigated theoretically and verified experimentally through NMR and XRD characterization of the intermediate silyliumylidene transition‐metal coordination complexes.